Acetamide Selection of Kluyveromyces lactis Cells Transformed with an Integrative Vector Leads to High-Frequency Formation of Multicopy Strains - Read, Jeremiah D. (American Society for Microbiology, 2007)
The yeast Kluyveromyces lactis has been extensively used as a host for heterologous protein expression. A necessary step in the construction of a stable expression strain is the introduction of an integrative expression vector into K. lactis cells, followed by selection of transformed strains using either medium containing antibiotic (e.g., G418) or nitrogen-free medium containing acetamide. In this study, we show that selection using acetamide yields K. lactis transformant populations nearly completely comprised of strains bearing multiple tandem insertions of the expression vector pKLAC1 at the LAC4 chromosomal locus, whereas an average of 16% of G418-selected transformants are multiply integrated. Additionally, the average copy number within transformant populations doubled when acetamide was used for selection compared to G418. Finally, we demonstrate that the high frequency of multicopy integration associated with using acetamide selection can be exploited to rapidly construct expression strains that simultaneously produce multiple heterologous proteins or multisubunit proteins, such as Fab antibodies.